Applied Calculus for Business, Economics, and the Social and Life Sciences - Rosen Kenneth H.; Hoffmann Laurence D.; Bradley Gerald L. (American : McGraw-Hill, 2005)
The Expanded Eighth Edition of Applied Calculus for Business, Economics, and the Social and Life Sciences includes four additional chapters: - Chapter 8, Differential Equations - Chapter 9, Infinite Series and Taylor Approximations - Chapter 10, Probability and Calculus - Chapter 11, Trigonometric Functions The textbook meets the needs of instructors who cover topics in one or more of these four chapters together with material from the initial seven chapters. This is often a two-semester course. (The word "Applied" in this title distinguishes this volume from the shorter edition.)The book introduces calculus in real-world contexts; the primary goal is to provide a sound, intuitive understanding of basic concepts students need as they pursue careers in business, the life sciences and the social sciences
Keywords: Hệ thống điện--Truyền tải; Toán học; Toán học trong kinh doanh; Toán học kinh tế